Nuclear Power: Understanding the Economic Risks and Uncertainties - Kessides, Ioannis N. (2012)
This paper identifies the fundamental elements and critical research tasks of a comprehensive analysis of the costs and benefits of nuclear power relative to investments in alternative baseload technologies. The proposed framework seeks to: (i) identify the set of expected parameter values under which nuclear power becomes cost competitive relative to alternative generating technologies; (ii) identify the main risk drivers and quantify their impacts on the costs of nuclear power; (iii) estimate the nuclear power option value; (iv) assess the nexus between electricity market structure and the commercial attractiveness of nuclear power; (v) evaluate the economics of smaller sized nuclear reactors; (vi) identify options for strengthening the institutional underpinnings of the international safeguards regime; and (vii) evaluate the proliferation resistance of new generation reactors and fuel cycles.